The place of artificial intelligence technologies in the modern society - Dabrarodni, Danila G.; Verashchaka, Aliaksei I. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
Artificial intelligence technologies (AIT) are increasingly manifesting themselves in various spheres of society. There are more and more situations when AIT perform functions that were previously performed only by a man, but at the same time they do not have the appropriate status to be considered a social subject, the author of a work or be responsible for the actions committed. The question about the status of AIT arises, that is, about the nature of the relations of such objects with other social actors, about the norms governing these relationships, about mutual responsibility. In this regard, attempts are being made around the world to establish the legal status of AIT and legal regulation in this area. However, in our opinion, legal regulation should be based on understanding of the ontological and social place of AIT, that is, on understanding of the specifics of such objects as forms of being, their social roles and functions in the system of social ties and relationships. Modern philosophical concepts will help us in understanding the unique state of AIT (research of science and technology, actor-network theory and postphenomenology). In the end of this article the main conditions and principles of regulation in the field of production and distribution of AIT are formulated.
Keywords: philosophy of technology; artificial intelligence; artificial intelligence technologies (AIT); ontological and social status of AIT; regulation in the field of artificial intelligence; postphenomenology; actor-network theory